2012
DOI: 10.1111/j.1365-2869.2012.01062.x
|View full text |Cite
|
Sign up to set email alerts
|

PER3 and ADORA2A polymorphisms impact neurobehavioral performance during sleep restriction

Abstract: SUMMARYThe objective of the study was to determine whether ADORA2A or PER3 polymorphisms contribute to individual responsivity to sleep restriction. Nineteen healthy adults (ages 18-39, 11 males, 8 females) underwent sleep restriction (SR) which consisted of seven nights of 3 h time in bed (TIB) (04:00-07:00). SR was preceded by seven in-laboratory nights of 10 h TIB (21:00-07:00) and followed by three nights of 8 h TIB (23:00-07:00). Volunteers underwent psychomotor vigilance, objective alertness, and subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…More recently, we found that this polymorphism related to individual differences in sleep homeostatic responses, but not to performance responses to chronic partial sleep loss [45]. By contrast, two very recent studies [14,20] reported that PER3 is related to individual differences in neurobehavioral responses to sleep restriction. It remains uncertain whether differences in important methodological details— including the need for much larger replicate subject samples—underlie the discrepancies relative to PER3 as a marker for neurobehavioral vulnerability to sleep loss.…”
Section: Phenotypic Differential Vulnerability To Sleep Lossmentioning
confidence: 84%
“…More recently, we found that this polymorphism related to individual differences in sleep homeostatic responses, but not to performance responses to chronic partial sleep loss [45]. By contrast, two very recent studies [14,20] reported that PER3 is related to individual differences in neurobehavioral responses to sleep restriction. It remains uncertain whether differences in important methodological details— including the need for much larger replicate subject samples—underlie the discrepancies relative to PER3 as a marker for neurobehavioral vulnerability to sleep loss.…”
Section: Phenotypic Differential Vulnerability To Sleep Lossmentioning
confidence: 84%
“…143,144 We showed that this polymorphism related to individual differences in sleep homeostatic responses, but not cognitive performance responses to chronic sleep restriction. 148 By contrast, two recent studies, 167,184 which used different sleep-restriction paradigms than that of Goel et al , 148 claimed that the PER3 VNTR polymorphism was related to individual differences in neurobehavioral responses to chronic sleep restriction. Notably, one of these 184 failed to include subjects from the critical PER3 5/5 putatively vulnerable genotype, and thus its findings must be interpreted cautiously and replicated in the appropriately inclusive genotypes.…”
Section: Sleep Deprivation and Performancementioning
confidence: 94%
“…Moreover, AKT1, a Ginsenoside Rb1 related gene, was related to diabetes. Furthermore, some related genes of other compounds of ginseng collected from the TCM-Mesh such as ADA, ADK, ADORA2A and GCG were reported to be associated with the sleep disorder 63, 64 and diabetes 6568 .
Figure 4The pharmacology network generated for ginseng. The innermost circle represents the compounds collected from the ginseng, the circle in the middle represented the related genes of compounds from ginseng, the outermost layer represented the diseases that were related to the genes.
…”
Section: Resultsmentioning
confidence: 99%